A Mechatronics System based on Feature Selection and AI for IoT Intrusion Detection Applications - Sharif, Montassar Aidi (International Journal of Integrated Engineering, 2022)
In today’s rapid development of the Internet, people’s daily life has become easier, but on the other hand, people’s privacy is also faced with potential threats if necessary security measures are not taken. To detect or stop cyberattacks in this area, network intrusion detection systems (IDS) can be equipped with machine learning algorithms to improve accuracy and speed. Recent research on intrusion and anomaly detection has shown that machine learning (ML) algorithms are widely used to detect malicious web traffic, using neural networks to learn models to visualize the sequence of connections between computers on a network. By analyzing and selecting the correct features, dense attacks can be detected more accurately, ultimately reducing misclassification rates and improving accuracy. In this study, we propose a Teacher-Student Feature Selection (TSFS) method that first uses the Isomap method to extract and select features in low dimensions and the best display, and then perform classification and the artificial neural MLP-Net for classification is used to minimize diagnostic errors. Although the teacher-student scheme is not new, to our knowledge, this is the first time this scheme has been used to select features in an intruder alert system. The proposed method can be used to select monitored and unmonitored features. The method is evaluated on different datasets and compared with the state-of-the-art feature selection methods available. The results show that the method performs better in classification, clustering and error detection. Furthermore, experimental evaluations show that the method is less sensitive to parameter selection.